Peran Koperasi Pesantren dalam Meningkatkan Pendapatan dan Kemandirian Ekonomi Santri: Studi Kasus pada Ponpes Imam Syafi'i Brebes - Anaty Anaty; M. Masrukhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Pesantren cooperatives serve as a crucial instrument in enhancing the income and economic independence of students (santri). This study aims to analyze the role of cooperatives in supporting the economic development of santri at Pondok Pesantren Imam Syafi'i Brebes. Using a qualitative case study approach, this research explores how pesantren cooperatives provide access to capital, entrepreneurship training, and market opportunities for santri. The findings indicate that pesantren cooperatives contribute to improving santri’s business management skills, expanding marketing networks, and fostering an entrepreneurial mindset. Additionally, cooperatives accelerate the process of economic independence by enabling santri to actively participate in productive economic activities. However, challenges such as a lack of business management knowledge and limited capital remain significant obstacles. Therefore, capacity-building strategies through training and policy support from the government and related institutions are essential to ensure the sustainability of pesantren cooperatives as a pillar of the Sharia-based economy Keywords: Economic independence, Entrepreneurship, Islamic economy, Pesantren cooperative, Santri.